CHARACTER BUILDING SEBAGAI MODEL KONSELING PASTORAL BAGI KAUM MUDA YANG MENGALAMI GAYA HIDUP SHOPAHOLIC - Jeni Palette; Yudha Nugraha Manguju (Institut Agama Kristen Negeri Manado, 2023)
Consumptive culture has become an inseparable part of the lifestyle of young people. The shopaholic phenomenon is very important to know the causes and how to overcome it, especially in the frame of pastoral counseling so that church residents can understand and understand shopaholic problems. This study uses qualitative methods by observing and conducting interviews with the aim of obtaining information about factors, impacts, and techniques that can be used in conducting pastoral counseling for young people who experience a shopaholic lifestyle in order to recover and minimize a distorted lifestyle by excessive shopping addiction. Shopaholic behavior is very detrimental to young people from various aspects such as psychic, financial, moral, spiritual, and social. This deviant behavior is caused by a disorder in individuals, namely compulsive obsessions characterized by repetitive thoughts that cause them to want constantly to immediately fulfill their shopping desires. The character-building technique can be practiced by building emotional closeness and building a model of spirituality as a model of Christian character.